Comparative Analysis of Bottom-Up and Top-Down Approaches in Forest Fringe Management: Evidence from Tanjung Betung II Village, Bengkulu, Indonesia - Anita Marianata (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
This study aims to evaluate the comparative effectiveness of bottom-up and top-down approaches in the management of forest fringe areas in Tanjung Betung II Village, Padang Guci Hulu District, Kaur Regency, Bengkulu Province. The study was motivated by persistent resource management friction, limited community participation, weak inter-agency institutional coordination, and unsustainable forest utilization within peripheral communities. Adopting a qualitative case study design, data were collected through in-depth semi-structured interviews, direct field observation, institutional documentation, and literature analysis involving village officials, traditional (adat) leaders, forest farmer groups (Kelompok Tani Hutan), and local forestry administrators. The findings demonstrate that while the top-down approach offers high regulatory standardization and uniform administrative control, it generates low social legitimacy, fails to accommodate localized ecological-economic needs, and produces fragile program sustainability. Conversely, the bottom-up approach is significantly more effective in strengthening community participation, leveraging traditional local wisdom (kearifan lokal), and establishing robust local ownership. This research advances public policy discourse by demonstrating that an isolated approach is insufficient; rather, an integrated collaborative governance model that bridges formal state regulations with community-based institutional arrangements is essential for sustainable forest fringe ecosystem management.